Fixed point automatic interpretation of bender-based G(0) measurements - Moldovan, Ionut Dragos (2017)
We present a new model updating technique for the automatic calculation of the small strain shear modulus of geomaterials, based on bender element experiments. The technique searches for the shear modulus that maximizes the correlation between the output signal obtained from the experiment and the output signal acquired from its computational simulation. Instead of conventional extremum finding algorithms, a fixed point technique is used to update the shear modulus at each iteration. This option increases substantially the attraction basin of the absolute maximum correlation and improves the convergence of the algorithm. (C) 2017 Elsevier Ltd. All rights reserved.